Peran Pendidikan Agama Islam Dalam Membentuk Karakter Generasi Milenial - Pina Pina; Hasnita Hasnita; Sutriana Sutriana; Darmawati Taro; Amaluddin Amaluddin (Journal of Humanities, Social Sciences, and Education, 2025)
The development of digital technology and globalization has brought significant changes to the mindset, behavior, and lifestyle of the millennial generation. This condition presents challenges in maintaining the moral values, ethics, and morals of the younger generation. Islamic Religious Education (PAI) plays a strategic role in shaping noble character through an approach to spiritual, moral, and social values ​​based on the Qur'an and Hadith. This literature study aims to examine the role of PAI in shaping the character of the millennial generation through curriculum, learning methods, educational environment, and the use of digital technology. Data were collected through a review of indexed international and national journals over the past five years. The results of the study indicate that Islamic Religious Education can shape religious character, discipline, responsibility, tolerance, and digital ethics when integrated with innovative learning approaches, such as project-based learning, digital learning, teacher role models, and collaboration between schools, families, and the community. The implementation of digital-based PAI has proven effective in reaching the learning patterns of the millennial generation, which tend to be visual, fast, and interactive. Thus, Islamic Religious Education plays a crucial role in developing a millennial generation with noble character, integrity, and readiness to face the challenges of the modern era. This study recommends strengthening the curriculum, improving teacher competency, and utilizing technology in learning as strategies to build the character of a religious and globally competitive millennial generation.